(untitled) (Global Journal of Science Frontier Research, 2012)
The Life Origination Hydrate hypothesis (LOH-hypothesis) presents a mechanism of living matter origination from simple mineral substances within natural underground or underseabed methane-hydrate matrixes with no external energy. The mechanism is well-founded chemically, thermodynamically, and logically and is applicable to any celestial body where the corresponding temperature and mineralogical conditions are maintained at a constant level for a rather long time. The hypothesis formulation method is based on the thermodynamic directedness of the natural movement and consists in an attempt to double back mentally the way Nature went and thus to reveal the principal milestones on its route.